2009
DOI: 10.1007/s11434-009-0632-2
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between cognition and emotion

Abstract: Cognition and emotion have long been thought of as independent systems. However, recent research in the cognitive and neurobiological sciences has shown that the relationship between cognition and emotion is more interdependent than separate. Based on evidence from behavioral and neuroscientific research, researchers have realized that it is necessary to propose a new conceptual framework to describe the relationship between cognition and emotion. In this article, recent research from behavioral, neuroscientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 88 publications
(167 reference statements)
1
27
0
Order By: Relevance
“…The second decomposition step is associated to the broad peak in the TIC between 230 and 450 °C range with a maximum at 396 °C. The mass spectrum recorded at 396 °C reveals a vast array of m/z signals up to 98 Da, with more intense signals (in decreasing order) at 28,18,15,16,44,45,27,43,29,39,75, and 97 Da ( Figure S2, Supporting Information). A more detailed characterization will require additional gas-chromatographic separation of the gaseous mixture.…”
Section: Thermogravimetric Analysis Coupled With Mass Spectroscopy Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The second decomposition step is associated to the broad peak in the TIC between 230 and 450 °C range with a maximum at 396 °C. The mass spectrum recorded at 396 °C reveals a vast array of m/z signals up to 98 Da, with more intense signals (in decreasing order) at 28,18,15,16,44,45,27,43,29,39,75, and 97 Da ( Figure S2, Supporting Information). A more detailed characterization will require additional gas-chromatographic separation of the gaseous mixture.…”
Section: Thermogravimetric Analysis Coupled With Mass Spectroscopy Ofmentioning
confidence: 99%
“…However, reported FT-IR spectra of thiophene or polythiophene show that the thiophene ring's characteristic absorption peaks such as bending vibration of in-plane CCH exist in both DVT and PMHS-DVT at 1409 and 1466 cm −1 peaks. [29] Comparing the FT-IR spectra of reactants with that of the product we notice major changes. First, the CH vibrational characteristics for vinyl groups [27] (wave numbers above 3000 cm −1 ) vanished, while those bands just below 3000 cm −1 , as typical for aliphatic CH vibration, remained.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The slurry was then ultrasonicated for 1 h, and mixed with thiophene (0.625 mL, Aldrich) cetyltrimethylammonium bromide (0.515 g, Aldrich), triethanolamine (1.32 g, Aldrich), and de-ionized water (7.5 mL) under 30 min ultrasonication. Subsequently, an ammonium persulfate solution (2.07 g in 5 mL water, Aldrich) was added dropwise into the mixture to synthesize the carbon-supported polythiophene (PTh/C) [21]. The mixture was then heated to 70°C in a water bath for 24 h. Each metal precursor (IrCl 3 , RuCl 3 , (NH 4 ) 2 PdCl 4 , Co(NO 3 ) 2 , FeCl 3 NiCl 2 , SnCl 4 , precursor:thiophene mole ratio = 1:4, which were all purchased from Aldrich except for (NH 4 ) 2 PdCl 4 from Alfa Aesar), was added separately to the PTh/C slurry with constant stirring at 80°C for 1 h. The pH of the mixture was increased to 11 by adding NaOH followed by chemical reduction of the metal precursors with the addition of sodium borohydride (NaBH 4 , Fluka) in excess under constant stirring for 2-3 h. The prepared metal-incorporated PTh/C catalysts (M-PTh/ C) were collected by filtration and then washed repeatedly with de-ionized water until the mixtures were neutralized (pH = 7).…”
Section: Synthesis Of Polymer-compositementioning
confidence: 99%
“…However, recent studies on cognitive science and neurobiology have shown that cognition and emotion are interdependent and influent each other, there are complex internal links. Scientists have realized that it is necessary to propose a new conceptual framework to describe the relationship between cognition and emotion [1].…”
Section: Introductionmentioning
confidence: 99%